Spiritual-Based Psychoeducation Increase of the Level Resilience of Youth Victims of Bullying - Betie Febriana; Dwi Heppy Rochmawati; Abdurrohim Abdurrohim; Mohammad Farhan (GLOBAL HEALTH SCIENCE GROUP, 2021)
In general, bullying has negative effects on victims, including increased anxiety, decreased self-esteem, self-distrust and depression. These things will affect to the concentration of student learning which ultimately leads to decrease learning achievement and more risk of suicide in adolescents. Therefore, developing the resilience of youth victims of bullying is needed to provide therapeutic coping to avoid these adverse effects. This study aims to determine the effectiveness of Spiritual-based psychoeducation therapy on the Level of Resilience of Youth Victims of Bullying. This is quasy experimental pre-post test research with total sampling. The sample is high school students who have experienced bullying in the past month, are physically healthy, and have no disabilities. The sample of this study was 50 and has been divided into two groups, namely the intervention group and the control group. This research used questionnaire’s ability of resilience in adolescents by Gail M wagnild and Heather M. Young. The results showed a significant effect of psychoeducation spiritual therapy on the level of adolescent resilience (p-value is 0.000 by Kolmogorov Smirnov). Schools need to consider this therapy as a choice to be applied to student victims of bullying.